A role of activating of lipid peroxidation and depression of the antioxidant systems of organism is in pathogeny of toxic action of lead (Experimental biology, 2015)
A plasmatic membrane of cells the basic place of application of many poisons. The ecological toxins of different naturerender the destabilizing action the membrane structures of cells, influence on the course of enzyme reactions on itssurface, change the barrier and receptor functions of membrane, what results in dysfunction of metabolism of cells.Lipid peroxidation, providing the physiological state of cellular membranes, not infrequently activates under the action of different toxins. Activation of lipid peroxidation is the universal mechanism of damage of cellular and subcellularmembranes.One of the possible ways in the pathogenesis of the toxical action of lead is the destabilization of cellular membranes,strengthening of free radical reactions, where the initiator of lipid peroxidation is the lead. Prolonged or intensive activation of lipid peroxidation leads to an increase expense of antioxidant enzymes, followed by a breakdown ofantioxidant protection.
Keywords: lipid peroxidation; antioxidant system; lead